The Role of Influencer Academy's Content Creator Class in Improving High School Students' Public Speaking Ability - Dwi Andriani, Astri; Husnul Chotimah, Destiana; Siti Fauziah, Syifa (The International Journal of Education Management and Sociology, 2023)
This research is entitled Analysis of Public Speaking Training for Teenagers – Case Study of Content Creator Influencer Academy Class Participants. The problems in this study are (1) What is the motivation of participants to take the Content Creator Influencer Academy Class? (2) How is the students' understanding of public speaking? (3) What are the factors that influence Content Creator class participants in doing public speaking? The purposes of this study are (1) to determine the motivation of participants to take part in the Content Creator Influencer Academy class, (2) to determine the understanding of the content creator class participants in public speaking, and (3) to determine the factors that influence the content creator class participants in doing public speaking. This research uses qualitative research methods using a case study approach. The results of this study indicate that participants have various motivations to take Content Creator classes ranging from awareness of responsibility for the information conveyed, wanting to hone skills to be part of the television world to wanting to explore the opportunities promised by social media. Participants already have a basic understanding of public speaking skills since school, but their understanding is increasing when they take this Content Creator – Influencer Academy class. Some factors influence participants when doing public speaking. These factors are divided into 2, namely internal and external factors.